AZ-801 configuring Windows server hybrid advanced services - Pluta, Charles; Goodwin, Sophia (Packt Publishing, 2024)
Dive deep into the world of Windows security with this comprehensive course designed for IT professionals. Starting with an overview, you will explore the configuration and management of Microsoft Defender, ensuring your servers are protected against the latest threats. Learn how to implement robust security measures using Group Policies, configure password policies, and secure domain controllers, providing a strong defense against unauthorized access. The journey continues with mastering Windows failover clusters. Understand how to implement and manage these clusters, configure storage and networking, and ensure high availability for your critical applications. You will also learn how to upgrade to Windows Server 2022 and utilize Windows Admin Center for efficient cluster management. This section equips you with the skills to maintain and recover clusters effectively. In the later sections, the course focuses on Windows Server recovery and migration. Discover how to manage backups with Azure, configure recovery options for both on-prem and Azure VMs, and handle Hyper-V replication and failover. The migration modules guide you through transferring data, using Storage Migration Service, and migrating various workloads to Azure, ensuring a smooth transition to modern infrastructure.
Online resource; title from title details screen (O'Reilly, viewed June 3, 2024)
Keywords: Microsoft Windows server -- Study guides -- Examinations; Windows Azure -- Study guides -- Examinations; Instructional films; Nonfiction films; Internet videos; Films de formation; Films autres que de fiction; Vidéos sur Internet